Теоретичне осмислення реконструкції в контексті повоєнного розвитку територій України - Підоричева, І.Ю.; Баш, А.С. (Економіка промисловості, 2025)
На основі аналізу динаміки частоти використання терміна «реконструкція» у друкованій англомовній літературі за 1860—2022 рр. виявлено його зв’язок із шоками, кризами та діями щодо подолання їх наслідків, а також із позитивними суспільними трансформаціями. Поглиблено розуміння сутності реконструкції шляхом визначення базових і комбінованих типів змін, які їй притаманні, розкрито контекстуальну багатозначність цього терміна. Дана типологія містить структурований набір варіантів реконструкції для практичного застосування при стратегічному плануванні відновлення територій. У результаті порівняльного аналізу реконструкції з низкою дотичних понять визначено їх спільну рису та змістовні розбіжності. This study analyzed the temporal dynamics of the relative frequency of the term “reconstruction” in English-language printed literature from 1860 to 2022. The analysis revealed that its usage was primarily associated with negative events of regional or global scale — such as wars, military conflicts, natural disasters, and economic crises — and efforts to address their consequences. Additionally, the term was linked to positive societal transformations related to decolonization, urbanization, and sustainable development. Understanding of the reconstruction concept has been enhanced through synthesizing its definitions found in scholarly, regulatory, and informational sources. This involved identifying of its core and composite types of change and the term’s contextual polysemy. The proposed typology of changes that reflect the essence of reconstruction may serve as a framework for analysis and decision-making, particularly in the selection of priority recovery projects for regions and communities. Building on the postulates and principles of O. Vyshnevskyi’s General Theory of Strategizing, this typology is integrated with the main branches of contemporary philosophy (ontology, epistemology, and axiology), which enables the identification of the most appropriate type of change aligned with the mission, vision, and values of a specific territory. Such an integrated approach ensures a scientifically grounded choice of reconstruction strategy (ranging from adaptive recovery for stable territories to comprehensive recovery for the most severely affected regions) and contributes to improving the quality of strategic planning in the field of regional development. A comparative analysis of reconstruction and related concepts was conducted, identifying their common feature and conceptual distinctions across five criteria: depth of change, scale of change, object of change, time horizon, and initiator of change. Despite their formal semantic similarity, most English-language terms commonly used as synonyms for “reconstruction” (such as “recovery”, “rebuilding”, “renovation”, “restoration”, “regeneration”, and “rehabilitation”) operate according to different change logics and have more limited applications. The analysis also found that the term “recovery” dominates in frequency of use in English-language printed literature. However, this stems not from its conceptual precision in describing recovery processes, but from its political appeal and linguistic simplicity. Of all related concepts, reconstruction encompasses the broadest range of changes, including both physical-spatial and functional transformations — at the levels of improvement and/or transformation — designed to mitigate the destructive impacts of shocks and crises or to facilitate societal transformations. These conceptual differences carry practical implications: terminological inaccuracy directly affects the quality of strategic planning, while term substitution may result in a narrowing of strategic vision and distortion of development priorities for territories.